MEDICALIZAÇÃO E PATOLOGIZAÇÃO DA/NA PRIMEIRA INFÂNCIA: CONVERSAS SOBRE PRÁTICAS PEDAGÓGICAS NÃO MEDICALIZANTES - Oliveira, Adriana Cristina Gomes (2022)
This is a master's research, started in the midst of the Covid-19 Pandemic, and therefore permeated by the challenges of sanitary biosecurity protocols. It is proposed to seek powerful perspectives of investigation and dialogue in an institution of Early Childhood Education in the city of Vitória, Espírito Santo, about how the processes of medicalization and pathologization have been built in the school routine, aiming to understand how the diagnoses and medical reports are generated in the contexts of a Municipal Center for Early Childhood Education and to what extent they are intertwined with pedagogical practices. The research is qualitative in nature and developed through a case study in which the following data was used as production instruments: conversation circles, semi-structured interviews and narratives of subjects and participants. The theoretical framework is composed by Moysés and Collares (2013, 2015), IIlich (1975), Untoiglich (2014), Sarmento (2000, 2004, 2007), Meirieu (2002, 2005), Tardif (2002), among others. Among the analyses, initially, we highlight the lightning transformation of originali historical-social issues, into merely biological and individual, disregarding the events around the child and focusing on the so-called “problems” of behavior, as well as the medical discourse rooted in the educational field, when there is a need to search for medicine to explain the child's behavioral issues, accompanied by a “medicine” to calm down; Another important analysis to be considered is the fact that the Diagnostic and Statistical Manual of Mental Disorders (DSM - 5) strengthens in biological terms the pathologization of life and childhood by bringing the idea of precocity in the prevention of possible “disorders”, taking as reference the child's behavior. In this context, we emphasize what has been pointed out in our research from the authors, with whom we have dialogued, that is, the displacement, often, of a political-pedagogical and social discussion for the search for quick solutions in drug treatments. The educational product is materialized in a “Pedagogical Notebook” whose purpose is to contribute to the dissemination of scientific knowledge on the subject of medicalization of education, as well as to encourage discussion about the intertwining of pedagogical practices in this process, with the aim of promoting non-medicalizing practices in the educational field.